A NEW SPECIES DIPLOPYLIDIUM UDGIRENSIS N.S.P. (EUCESTODA : DIPYLIDIIDAE) FROM FELIS DOMESTICUS AT UDGIR, INDIA. - PAWAR, S. B.; SHINDE, G. B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Diplopylidium udgirensis in. sp. collected from Felis domesticus at Udgir Distt. Latur, differs from all species, but it comes closer to D. genettae in number of testes (480 - 500). It, however, differs from same in size length, number of rostellar hooks, crowns of hooks and position of genital aperture. Seven worms were collected from intestine of Felis domesticus at Udgir, India, and after going through the literature, erected a new species of genus Diplopylidium Beddard 1913.